Privilege, Decentring and the Challenge of Being (Non-) Indigenous in the Study of Indigenous Issues - Olsen, Torjer A. (The Australian Journal of Indigenous Education, 2017)
There are acceptable ways of studying Indigenous issues as a non-Indigenous scholar. Still, the role and identity of the scholar is important and debated within the study of Indigenous issues. The purpose of this article is to accept, but explore the premise of a distinction between Indigenous and non-Indigenous. I claim the possibility of taking a decentred space within Indigenous studies and move towards a methodological and theoretical foundation that is informed by scholars with different stances and backgrounds. A key approach is the intersectional approach to privilege. Neither privilege/oppression, Indigenous/non-Indigenous, nor insider/outsider are binary relations. From Indigenous methodologies such as kaupapa Māori, I emphasise, in particular, the local starting point, arguing that this is the way to transfer relevant issues to a bigger context.